2018
DOI: 10.1038/s41598-018-34433-4
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Carcinogenic Effects of Circadian Clock Gene BMAL1

Abstract: The circadian clock confers daily rhythmicity on many biochemical and physiological functions and its disruption is associated with increased risks of developing obesity, diabetes, heart disease and cancer. Although, there are studies on the role of Bmal1 in carcinogenesis using germline, conditional or tissue-specific knockouts, it is still not well understood how BMAL1 gene affects cancer-related biological events at the molecular level. We, therefore, took an in vitro approach to understand the contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 53 publications
(87 reference statements)
4
39
0
Order By: Relevance
“…Since tumor hypoxia and acidosis are well-known to promote tumor metastasis in cancers including MDA-MB-231 cells, targeting the tumor hypoxia and acidosis is likely important in treating tumors [40][41][42][43]. Interestingly, the previous study reported that knocked-out BMAL1 promotes metastasis in MDA-MB-231 cells, and previously our results showed that BMAL1 was reduced by tumor hypoxia-induced acidosis and recovered by selectively targeting the acidic pH in breast cancer cells [19]. Based on these references and our results, we hypothesized that promoted metastasis under acidosis is caused by a decrease of BMAL1, and maintaining BMAL1 by buffering acidic pH is a therapeutic approach to prevent metastasis.…”
Section: Tumor Acidosis-mediated Decrease Of Bmal1 Promotes Metastatisupporting
confidence: 47%
See 2 more Smart Citations
“…Since tumor hypoxia and acidosis are well-known to promote tumor metastasis in cancers including MDA-MB-231 cells, targeting the tumor hypoxia and acidosis is likely important in treating tumors [40][41][42][43]. Interestingly, the previous study reported that knocked-out BMAL1 promotes metastasis in MDA-MB-231 cells, and previously our results showed that BMAL1 was reduced by tumor hypoxia-induced acidosis and recovered by selectively targeting the acidic pH in breast cancer cells [19]. Based on these references and our results, we hypothesized that promoted metastasis under acidosis is caused by a decrease of BMAL1, and maintaining BMAL1 by buffering acidic pH is a therapeutic approach to prevent metastasis.…”
Section: Tumor Acidosis-mediated Decrease Of Bmal1 Promotes Metastatisupporting
confidence: 47%
“…There has been extensive research to overcome breast cancer metastasis, but it has not been adequately solved. According to previous reports, circadian genes, which are significantly reduced in cancer, suppress tumor progression including metastasis [16][17][18][19]. For this reason, we wanted to find a way to recover the reduced circadian genes in cancer to increase the survival rate by preventing metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PER2 mutant cells harbour a functional circadian oscillator, whereas BMAL1 is the only gene whose deletion alone leads to complete loss of rhythmicity. In contrast to PER2 mutant cells, apoptosis is enhanced in BMAL1 mutant breast epithelial cells, in response to chemotherapeutic agents, Cisplatin and Doxorubicin . This suggests that interfering with BMAL1 expression and abolishing circadian rhythms might be protective against tumour initiation following DNA damage insults.…”
Section: The Circadian Clock Genes Regulate Apoptosismentioning
confidence: 99%
“…Studies have shown that inhibition of CRY1 , PER2 or BMAL1 results in enhanced cell migration or invasion via the Akt signalling pathway, in osteosarcoma ( CRY1 and PER2 ) and lung cancer and glioma cells ( BMAL1 ). In addition, BMAL1 knockout, resulting in loss of circadian rhythmicity, results in increased invasion of breast cancer cells . The EMT is a key step in cancer progression, and enables cancer cell invasion and metastasis.…”
Section: The Circadian Clock Influences Epithelial‐to‐mesenchymal Tramentioning
confidence: 99%